Bilateral inferior turbinate necrosis and septal perforation as a complication of nasal packing and sphenopalatine artery ligation for intractable epistaxis - Eves, Peter J.; Wright, Brendan; Adair, Robin A. (International Surgery Journal, 2025)
A male patient in his mid-70s was referred to ENT services at a regional centre with severe epistaxis. After failing conservative management, including nasal cautery and bilateral packing, the patient proceeded to have an uncomplicated left sphenopalatine artery (SPA) ligation. Six months later he developed nasal blockage and crusting and blew a large amount of foul-smelling necrotic tissue from his nose. Examination and investigation findings revealed loss of most of his nasal septum and both inferior turbinates. This occurred as a rare complication of nasal packing and SPA ligation causing ischaemic necrosis.